Relevance of a Truncated PRESENILIN 2 Transcript to Alzheimer's Disease and Neurodegeneration. - Moussavi Nik, Seyyed Hani; Porter, Tenielle; Newman, Morgan; Bartlett, Benjamin; Khan, Imran; Sabale, Miheer; Eccles, Melissa; Woodfield, Amy; Groth, David; Doré, Vincent; Villemagne, Victor L; Masters, Colin L; et al. (J Alzheimers Dis, 2021)
BACKGROUND: The PRESENILIN genes (PSEN1, PSEN2) encoding for their respective proteins have critical roles in many aspects of Alzheimer's disease (AD) pathogenesis. The PS2V transcript of PSEN2 encodes a truncated protein and is upregulated in AD brains; however, its relevance to AD and disease progression remains to be determined. OBJECTIVE: Assess transcript levels in postmortem AD and non-AD brain tissue and in lymphocytes collected under the Australian Imaging Biomarker and Lifestyle (AIBL) study. METHODS: Full length PSEN2 and PS2V transcript levels were assessed by quantitative digital PCR in postmortem brain tissue (frontal cortex and hippocampus) from control, AD, frontotemporal dementia (FTD), and Lewy body dementia (LBD). Transcript levels were also assessed in lymphocytes obtained from the Perth subset of the AIBL study (n = 160). Linear regression analysis was used to assess correlations between transcript copy number and brain volume and neocortical amyloid load. RESULTS: PS2V levels increased in AD postmortem brain but PS2V was also present at significant levels in FTD and LBD brains. PS2V transcript was detected in lymphocytes and PS2V/PSEN2 ratios were increased in mild cognitive impairment (p = 0.024) and AD (p = 0.019) groups compared to control group. Increased ratios were significantly correlated with hippocampal volumes only (n = 62, β= -0.269, p = 0.03). CONCLUSION: Taken together, these results suggest that PS2V may be a marker of overall neurodegeneration.